Evaluation of Antidiarrhoeal Activity of Thunbergia fragrans Roxb. - SHESHADRI SHEKHAR, D.; ASHOK KUMAR, B.S.; SURESH, N.; DHANASEKARAN, S. (Asian Journal of Chemistry, 2010)
Acetonic and ethanolic extracts of Thunbergia fragrans (Acanthaceae) leaves on gastrointestinal motility was investigated by using Swiss albino mice. Acetonic and ethanolic extracts at dose of 500 mg/kg body weight were orally administered to mice. The antidiarrhoeal activity was evaluated using charcoal meal model and castor oil induced diarrhoea model in albino mice. Both extracts demonstrated a significant antidiarrhoeal activity (p < 0.001). These observations prove the antidiarrhoeal activity of T. fragrans. The acute toxicity studies of these two extracts upto a dose level of 2000 mg/kg body weight of the mice showed no mortality.